Power Oligarchy: The Game of Cartel in Cooking Oil Scarcity - Fatihani Baso; Andi Yaqub; Andi Novita Mudriani Djaoe; Ashadi L. Diab (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
Allegations related to the cartel arise every time Indonesia experiences a shortage of cooking oil. The study aims to discuss the causes of the scarcity of cooking oil in Indonesia. Is it because of Permendagri Number 06 of 2022 or because of a cartel or is it caused by an artificial scarcity made by a syndicate? And whether this cartel and scarcity have anything to do with it. The study used qualitative research. The study uses normative or socio legal by analyzing relevant sources and news related to the scarcity of cooking oil. The results showed that the cause of the scarcity of cooking oil was the highest retail price which was marked by the issuance of Permendagri No. 6 of 2022, the law of one price which causes arbitrage, artificial scarcity by businessman, panic buying among the public, conditional sales and distribution problems. The relationship between the cartel and the scarcity of cooking oil lies in its complex and non-transparent distribution to consumers. The cartel group restrains the widely circulated cooking oil products with HRP because the businessman will lose out automatically if sold at HRP. Therefore, businessman withdraw products from the market and resulting in scarcity.